Three-generational families: Are they beneficial to Chinese children's creativity?. (March 2020) - Pang, Weiguo; Lu, Ye; Long, Haiying; Wang, Qing; Lin, Lijia
Highlights: The co-parenting of grandparents and parents had a negative effect on children's creativity. Children growing up in the three-generation families had lower creativity than those from families living without grandparents. Compared with girls, boys raised in the three-generation families were more likely to show disadvantages in creativity development. Only children overall showed significantly higher creativity than children with siblings. Only children's advantage was more salient for those raised in nuclear families than in three-generation families. Abstract: It is not uncommon in China that children are raised by both parents and grandparents in an extended family. The purpose of this study is to investigate the effects of three-generational families on Chinese children's creativity. A sample of 1710 elementary school students aged 6–13 was drawn from two schools in urban districts of Shanghai. Participants' creativity was measured by the Torrance Test of Creative Thinking-Figural (TTCT-Figural) and Alternate Uses tasks (AUT) and their family demographic information was obtained from parents' report. The results indicated that (1) the co-parenting of grandparents and parents had a negative effect on children's creativity; (2) children growing up in the three-generation families, particularly in the grandparents-headed families, had lower creativity than those from families living without grandparents; (3) compared with girls, boys raised in the three-generation families were more likely to show disadvantages in creativity development; (4) only children overall showed significantly higher creativity than children with siblings, but this advantage was more salient for only children raised in nuclear families than in three-generation families. These results are explained on the basis of parental investment theory. We further conclude that the quality of cognitive and interpersonal resources in a family, such as intellectual stimulation and general encouragement, matter more than the simple accumulation of family resources in predicting children's creativity.